(untitled) (Training and Practice : Journal of Educational Sciences, 2019)
In our paper we analyse two schoolbook series: Kon-Takt and Schritte international. These schoolbooks are for German as foreign language teaching from a Hungarian and an international publisher. This is a reason why there are differences between their language teaching methods. Our research has four main points: (1) the development of language skills and grammatical correctness, (2) the usage of other (foreign) language knowledge in foreign language learning, (3) language learning motivation and (4) the usage of digital tasks. According to our results, Schritte international has an advantage in the developed foreign language learning view from Germany but Kon-Takt is closer to the characteristics and claims of Hungarian pupils.